Stromal Bed Thickness Measurement During Laser in Situ Keratomileusis Using Intraoperative Optical Coherence Tomography. Issue 4 (April 2015) - Ye, Cong; Yu, Marco; Jhanji, Vishal
Abstract : Purpose: The aim of this study was to compare repeatability and agreement of stromal bed thickness (SBT) measurements with intraoperative spectral domain optical coherence tomography (SD-OCT) and ultrasound pachymetry (USP). Methods: The SBT was measured in 14 eyes of 14 patients during femtosecond laser in situ keratomileusis (LASIK). Intraoperative SD-OCT was positioned on the eye to acquire images after creation of LASIK flaps. Patients were then asked to sit in front of a swept-source optical coherence tomography (SS-OCT) for measurements. Subsequently, LASIK flaps were lifted and SBT was measured with USP. Three readings were obtained with each instrument. Repeatability of measurements was evaluated by the intraclass correlation coefficient (ICC) and reproducibility coefficient (RC). Results: ICC and RC values of SBT measurements were 0.98 and 8.7 μm, 0.99 and 7.1 μm, and 0.99 and 6.9 μm, respectively, for SD-OCT, SS-OCT, and USP. There were no significant differences in the RC between the devices. The ICCs for agreement of SBT measurement were 0.97 between SD-OCT and SS-OCT, 0.8 between SD-OCT and USP, and 0.8 between SS-OCT and USP. The 95% limits of agreement of SBT measurements were −13.1 to 8.8 μm between SD-OCT and SS-OCT, −48.7 to 31.4 μm between SD-OCT and USP, and −42.8 to 29.8 μm between SS-OCT and USP. Conclusions: SBT measurements obtained with intraoperative SD-OCT, SS-OCT, and USP were highly repeatable. Optical coherence tomography may be used as a potential noncontact device for corneal thickness assessment during LASIK. However, optical coherence tomography tends to underestimate the SBT compared with USP, and these measurements may not be used interchangeably. Abstract : Supplemental Digital Content is Available in the Text.